Fungal plant pathogen “mutagenomics” reveals tagged and untagged mutations in Zymoseptoria tritici and identifies SSK2 as key morphogenesis and stress-responsive virulence factor - Blyth, Hannah R.; Smith, Dan; King, Robert; Bayon, Carlos; Ashfield, Tom; Walpole, Hannah; Venter, Eudri; Ray, Rumiana V.; Kanyuka, Kostya; Rudd, Jason J. (Frontiers in Plant Science, 2023)
'Mutagenomics' is a combination approach of random mutagenesis, phenotypic screening, and whole-genome re-sequencing to uncover all tagged and untagged mutations linked with phenotypic changes in an organism. In this study, we performed a mutagenomics screen on the wheat pathogenic fungus Zymoseptoria tritici for altered morphogenetic switching and stress sensitivity phenotypes using Agrobacterium-mediated “random” T-DNA mutagenesis (ATMT). Biological screening identified four mutants which were strongly reduced in virulence on wheat. Whole genome re-sequencing defined the positions of the T-DNA insertion events and revealed several unlinked mutations potentially also affecting gene functions. Remarkably, two independent reduced virulence mutant strains, with similarly altered stress sensitivities and aberrant hyphal growth phenotypes, were found to have distinct loss of function mutations in the ZtSSK2 MAPKKK gene. One mutant strain had a direct T-DNA insertion affecting the N-terminus of the predicted protein, whilst the other possessed an unlinked frameshift mutation towards the C-terminus. We used genetic complementation to restore both strains' wild-type (WT) function (virulence, morphogenesis, and stress response). We demonstrated that ZtSSK2 has a non-redundant function with ZtSTE11 in virulence through the biochemical activation of the stress-activated HOG1 MAPK pathway. Moreover, we present data suggesting that SSK2 has a unique role in activating this pathway in response to specific stresses. Finally, dual RNAseq-based transcriptome profiling of WT and SSK2 mutant strains revealed many HOG1-dependent transcriptional changes in the fungus during early infection and suggested that the host response does not discriminate between WT and mutant strains during this early phase. Together these data define new genes implicated in the virulence of the pathogen and emphasise the importance of a whole genome sequencing step in mutagenomic discovery pipelines.